Dampak Evaluasi Kinerja Terhadap Self-Efficacy Calon Konselor Sekolah dalam Melaksanakan Konseling Individu: Pendekatan Mixed Method - Agustin, Adhi Krisna Maria; Mulawarman, Mulawarman; Sutarmi, Sutarmi (Jurnal Ilmiah Global Education, 2025)
This study examines the impact of performance evaluation (feedback) on the self-efficacy of counsellors in training in Indonesia using a mixed-method sequential explanatory approach. Quantitative analysis (SEM-PLS) revealed that feedback significantly influences self-efficacy (β = 0.323, p = 0.042), though with a modest effect size (R² = 10.4%). Qualitative findings identified three key themes: (1) constructive feedback (specific, solution-focused, and dialogic) as most effective, (2) self-reflection as a mediator, and (3) the critical role of a supportive environment. The study highlights the need for structured feedback rubrics, integrated reflection sessions, and collaborative evaluation practices to enhance self-efficacy. These findings contribute to the development of evidence-based training models for counselor preparation programs in Indonesia, addressing gaps in conventional evaluation systems.